Screening drought tolerance in potato germplasm resources in the northwestern region of China - Xiaoyun Li; Lei Luo; Xiaopeng Shi; Shigui Li; Lihui Wang; Deming Li; Fengxian Li (BMC Plant Biology)
Abstract Background Drought is one of the major factors affecting the growth and development of potatoes. Screening drought-tolerant potato germplasm is of great significance for drought tolerance research and the utilization of drought-tolerant germplasm resources. Results In this study, a two-year field evaluation of drought tolerance was conducted on 31 potato germplasm resources from 2023 to 2024. The experimental treatments included normal irrigation (NI) and drought stress (DS). A total of 24 indices related to potato morphology, photosynthesis, physiology, and yield were selected for drought tolerance evaluation. All indices exhibited varying degrees of change under drought stress. Correlation analysis revealed significant correlations among the drought tolerance coefficients of the 24 measured indicators. Principal component analysis was used to transform the 24 conventional indicators into six independent and comprehensive components, with a cumulative variance contribution rate of 86.38%. Using D-value cluster analysis, the 31 potato germplasm resources were classified into five categories: strong drought tolerance, moderate drought tolerance, intermediate drought tolerance, drought-sensitive, and extremely drought-sensitive. Stepwise regression analysis indicated that the following indicators could be used as objective evaluation criteria for drought tolerance in the mid-to-late growth stages of potatoes: fresh above-ground biomass, dry above-ground biomass, fresh below-ground biomass, dry below-ground biomass, chlorophyll content, relative chlorophyll content, net photosynthetic rate, stomatal conductance, superoxide dismutase activity, number of large tubers per plant, fresh tuber weight per plant, and plot yield. Conclusions Among them, the strong drought-tolerant materials included Long 10, D1595-7, Lin 18, Tong 31, and D16105-14. The results of this study provide theoretical references and practical guidance for potato drought-tolerant breeding, drought tolerance mechanisms, and drought-tolerant cultivation techniques.